2012
DOI: 10.1161/hypertensionaha.111.180554
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Incident Hypokalemia and Hyperkalemia in Treated Hypertensive Patients in the Antihypertensive and Lipid-Lowering Treatment to Prevent Heart Attack Trial

Abstract: Concerns exist that diuretic-induced changes in serum potassium may have adverse effects in hypertensive patients. ALLHAT, a large practice-based clinical trial made it possible to examine consequences of observed changes in potassium during care in conventional practice settings. Normokalemic participants randomized to chlorthalidone versus amlodipine or lisinopril as first-step drug were stratified by year-1 potassium. Post-year-1 outcomes among hypokalemics (potassium<3.5mmol/L) and hyperkalemics (potassium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 22 publications
2
46
1
Order By: Relevance
“…Thus, event rates in subjects with ESVEA and accompanying hypokalemia were almost 14× greater compared with the event rates seen when no ESVEA or hypokalemia were present. According to this study and previous studies, hypokalemia seems to be independently associated with a worse prognostic outcome in terms of cardiovascular-related events, 6,[17][18][19] and data from the present study suggest that mild hypokalemia interacts with excessive supraventricular ectopy to increase the risk of stroke significantly. Earlier studies has shown ESVEA as a predictor of atrial fibrillation and stroke.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Thus, event rates in subjects with ESVEA and accompanying hypokalemia were almost 14× greater compared with the event rates seen when no ESVEA or hypokalemia were present. According to this study and previous studies, hypokalemia seems to be independently associated with a worse prognostic outcome in terms of cardiovascular-related events, 6,[17][18][19] and data from the present study suggest that mild hypokalemia interacts with excessive supraventricular ectopy to increase the risk of stroke significantly. Earlier studies has shown ESVEA as a predictor of atrial fibrillation and stroke.…”
Section: Discussionsupporting
confidence: 84%
“…6 One of the suggested mechanisms is prolongation of the repolarization phase of the myocardial action potential because of a reduced repolarizing outward potassium current. 7,8 Prolongation of the repolarization phase can cause early after-depolarizations, which potentially could lead to arrhythmia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To the Editor: I read with interest the article by Alderman et al 1 on the clinical significance of hypokalemia and hyperkalemia in the antihypertensive treatment and prevention of cardiovascular complications. The conclusion was that, in most patients, concerns about potassium levels should not influence the clinician's decision about initiating hypertension treatment with low-moderate doses of thiazides.…”
Section: Serum Potassium Thiazides Aldosterone and Mineralocorticomentioning
confidence: 99%
“…The fact that hypokalemia and hyperkalemia each predict increases in mortality has been reported in multiple community studies and in studies of a variety of disease populations including hypertension, CKD, atherosclerosis, and others [3,4,5,6,7,8]. All of this suggests that closer monitoring of serum potassium and more aggressive prevention or correction/repletion of even modest hypo or hyperkalemia may be appropriate.…”
mentioning
confidence: 97%